A theoretical and experimental study of a TBAB salt hydrate based cold thermal energy storage in an air conditioning system. (October 2019) - Wang, Xiaolin; Zhai, Xiaoqiang; Zhang, Huanqi; Zhou, Lei
Highlights: A TBAB hydrate based cold storage is built in an emulated air conditioning system. A cold storage model is developed based on ε-NTU method and is used in TRNSYS. The effect of HTF and flowrate on charging rate and capacity is studied. The effect of HTF and cooling load on discharging rate and capacity is studied. The effect of PCM phase, coils' number and material is studied using ε-NTU model. Abstract: Various phase change materials (PCMs) have been studied in the past decade for cold thermal energy storage (CTES), among which semi-clathrate hydrates of quaternary ammonium salts have aroused great interests. Tetrabutylammonium bromide (TBAB) hydrates can form at temperatures applicable for air conditioning applications. Based on the results of former studies on a TBAB hydrate based PCMs, this paper investigates the influencing factors of a lab-scale CTES tank based on this self-developed PCM in an emulated air conditioning system. The effect of chilled water temperature and flowrate on charge, and the effect of return water flowrate and cooling load on discharge are experimentally studied. A model of the CTES was developed using ε-NTU method, through which its performance are evaluated in terms of charging/discharging rate, charging/discharging capacity and efficiency. In addition, influencing factors such as return water temperature and flowrate, initial PCM liquid fraction, and the number and material of the heat transfer coils are analysed using TRNSYS simulation employing the developed CTES model. According to the results, it is suggested in the actual use of TBAB hydrate based CTES to apply 2.0 °C chilled water for charge with initial solids and 4.0 °C chilled water for charge without initial solids. The optimal chilled water flowrate, 12 g s −1 for charge with initial solids and 18 g s −1 for charge without initial solids, can also be employed. In addition, in the design of a CTES the heat transfer coils are suggested to have a thermal conductivity close to 16 W m –1  K −1 but no need to exceed this value.